2022
DOI: 10.1108/lht-03-2022-0165
|View full text |Cite
|
Sign up to set email alerts
|

Impact of information credibility on social media information adoption behavior: a systematic literature review

Abstract: PurposeThe purpose of this systematic literature review was to collect and review the studies published worldwide in English language presenting the persuasive role of information/content credibility (IC) on the information adoption behavior (IAB) of social media users.Design/methodology/approachThe relevant literature was searched by the reviewers from two specialized databases, i.e. Library, Information Science and Technological Abstract (LISTA) and Library and Information Science Abstracts (LISA), whereas f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 111 publications
0
5
0
Order By: Relevance
“…It thus follows that COVID-19 information shared on social media that demonstrate high levels of credibility will encourage more users to adopt COVID-19 pandemic information on social media. Studies have confirmed that information credibility is significantly associated with information adoption on social media (Khan et al, 2022;Mensah et al, 2022). Consequently, H2 was put forward.Hypothesis 2:Information credibility positively influences the COVID-19 pandemic information adoption on social media systems.…”
Section: Information Credibilitymentioning
confidence: 93%
“…It thus follows that COVID-19 information shared on social media that demonstrate high levels of credibility will encourage more users to adopt COVID-19 pandemic information on social media. Studies have confirmed that information credibility is significantly associated with information adoption on social media (Khan et al, 2022;Mensah et al, 2022). Consequently, H2 was put forward.Hypothesis 2:Information credibility positively influences the COVID-19 pandemic information adoption on social media systems.…”
Section: Information Credibilitymentioning
confidence: 93%
“…Readers may be interested in reading recent articles on curriculum development for the Master of Public Administration (Ho et al, 2023a), urban governance (Zhang et al, 2023), IoT as a societal transformer (Chohan et al, 2023), open government data (Dai et al, 2023;Wu et al, 2022;Wang et al, 2023c) and knowledge management in governments (Lam et al, 2023). Khan et al (2024a) performed a systematic review and found a significant impact of information creditability on the information adoption behavior of social media users. Readers may be interested in reading recent articles on fake news and misinformation (Au et al, 2022;Ho et al, 2022Ho et al, , 2023aMeng et al, 2023;Mirzabeigi et al, 2023;.…”
Section: Public and Culturementioning
confidence: 99%
“…Khan et al (2024a) performed a systematic review and found a significant impact of information creditability on the information adoption behavior of social media users. Readers may be interested in reading recent articles on fake news and misinformation (Au et al , 2022; Ho et al ., 2022, 2023a, b, c; Meng et al , 2023; Mirzabeigi et al , 2023; Zhang et al , 2022).…”
Section: Public and Culturementioning
confidence: 99%
“…Readers may also be interested in recent research on communities of practice (Leung et al ., 2023; Wang and Xie, 2023; Zhang and Hu, 2024), MOOCs (Cheng, 2022; Cheng et al ., 2023; Wang et al , 2023b), social media information creditability and sharing issues (Khan et al , 2022; Li et al , 2023b; Ye and Ho, 2022; Yuan and Bi, 2023; Zhang et al , 2022, 2023b), and the use of social media for promotion (Liao et al , 2022; Lu et al , 2023; Wójcik, 2022a; Wu and Yang, 2022).…”
Section: Library and Information Support Of Contemporary Learning Beh...mentioning
confidence: 99%